PEREMPUAN DALAM FILM IN THE LAND OF BLOOD AND HONEY - Fatmawati Fatmawati (Texture:Art and Culture Journal, 2020)
This article studies the representation of women in In the Land of Blood and Honey movie, a romantic drama movie set in the background of the Bosnian war. By using feminist film theory, the article analyzes the depiction of women image associated with men and the resistance raised in the film. The results of the analysis show that Bosnian women experience oppression during the Bosnian. They are victims of kidnappings, raped, tortured, murdered and exploited in war. Resistance emerges from female character who escapes from Serbian army camp and decides to be a spy for Bosnian soldiers.